Mekanisme Proses Tahap Ekstraksi Karagenan Dari Eucheuma cottonii Menggunakan Pelarut Alkali (The Mechanism of Carrageenan Extraction from Eucheuma cottonii Using Alkaline Solvent) - Sperisa Distantina; Rochmadi Rochmadi; Wiratni Wiratni; Moh. Fahrurrozi (agriTECH, 2012)
Carrageenan recovery process was developed for Eucheuma cottonii by investigating the effects of distilled water, KOH (0.1-0.5 N) and NaOH (0.1-1.0 N) as the solvent on carrageenan yield and gel properties. Extraction process was carried out with a constant ratio of seaweed weight to solvent volume (1: 50; g/mL) at 80oC.  A certain amount of the liquid sample was withdrawn at regular interval time for analysis. Filtrate was separated from residue by pouring ethanol. The precipitated carrageenans were collected and oven dried at 50-60oC to a constant weight. The extraction product was found to have virtually identical infrared spectra to the reference samples of kappa-carrageenan. Distilled water was the most efficient solvent with regard to yield but certainly not gel strength. Increasing KOH concentration led to carrageenan containing less sulfate content. In extraction process using alkali, the ion exchange occurred between cation from alkali solution and anion from sulphate in the seaweed. Compared with cation of sodium, the cation of potassium was able to form helixes aggregation indicated by the higher gel strength value. Alkali concentrations affected the gel strength of the extracted carrageenan significantly.ABSTRAKPenelitian ini bertujuan mengembangkan proses ekstraksi karagenan dari rumput laut Eucheuma cottonii dengan mempelajari pengaruh jenis pelarut pada tahap ekstraksi, yaitu air suling, KOH, dan NaOH terhadap rendemen dan sifat gel karagenan.  Ekstraksi dilakukan dengan perbandingan bobot rumput laut – volume pelarut dijaga tetap yaitu 1:50 g/mL pada 80oC. Cuplikan diambil setiap interval waktu tertentu untuk dianalisis. Karagenan dalam filtrat diendapkan dengan etanol dan serat yang dihasilkan dikeringkan sampai bobot konstan. Spektrum infra merah menunjukkan bahwa karagenan yang dihasilkan identik dengan jenis kappa. Air suling merupakan pelarut yang efisien untuk mendapatkan rendemen yang tinggi, tetapi kekuatan gel karagenan yang dihasilkan rendah. Konsentrasi KOH semakin tinggi akan menghasilkan karagenan dengan kadar sulfat semakin rendah dan kekuatan gel meningkat.   Pada tahap ekstraksi menggunakan alkali, terjadi peristiwa pertukaran ion antara kation dalam pelarut dengan ion sulfat dalam rumput laut. Dibandingkan dengan kation Na, kation K mampu membentuk agregasi heliks yang terindikasi berdasarkan kekuatan gel yang lebih kuat.